2018
DOI: 10.3168/jds.2017-13682
|View full text |Cite
|
Sign up to set email alerts
|

Technical note: Changes in rumen mucosa thickness measured by transabdominal ultrasound as a noninvasive method to diagnose subacute rumen acidosis in dairy cows

Abstract: Feeding high-grain diets leads to the release and accumulation of short-chain fatty acids in the rumen. The subsequent prolonged decline in ruminal pH can lead to subacute ruminal acidosis (SARA). Accumulation of short-chain fatty acids can cause proliferation of rumen papillae to increase absorption surface, subsequently leading to a thickening of the rumen mucosa. The aim of this study was to evaluate the appropriateness of continuous measurements of the rumen mucosa thickness (RMT) as a diagnostic tool for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 12 publications
0
11
1
Order By: Relevance
“…For cattle, however, this topic was hardly ever investigated. The absorption capacity of the rumen wall is possibly more efficient in ≥4 L cows, because cows with more than three lactations have a thicker rumen epithelium then cows with three or less lactations [ 13 ]. Together with a bigger rumen, this provides them with potentially a higher number of papillae or larger rumen papillae, resulting in an increased absorptive surface [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For cattle, however, this topic was hardly ever investigated. The absorption capacity of the rumen wall is possibly more efficient in ≥4 L cows, because cows with more than three lactations have a thicker rumen epithelium then cows with three or less lactations [ 13 ]. Together with a bigger rumen, this provides them with potentially a higher number of papillae or larger rumen papillae, resulting in an increased absorptive surface [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research in recent years has indicated different susceptibilities to SARA among cows in different lactations [ 10 , 11 ]. One contributing factor to lesser susceptibility is an increase of the rumen-mucosa thickness, and thereby absorptive capacity, with the duration of concentrate feeding and with increased lactation numbers [ 12 , 13 ]. Another major contributing factor is the adaptation of the gut microbiome, of which the rumen and fecal microbiome vary in high and low producing dairy cattle [ 14 , 15 ] and with age [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In general, it is well known that the inclusion of high-concentrate diets causes an enlargement of ruminal papillae length and width (Černík et al, 2011;Zitnan et al, 2003). Recently, it has been suggested that the ruminal mucosa thickness might serve as diagnostic tool for SARA, because the enlargement of the ruminal mucosa can be visualised via transabdominal ultrasound, an equipment which is part of the practical diagnostic tools of veterinarians (Mirmazhari-Anwar, Sharifi, Mirshahi, Mohri, & Grünberg, 2013;Neubauer, Humer, Kröger, Meissl et al, 2017). A pilot study conducted by Mirmazhari-Anwar et al (2013) revealed a negative correlation between the ruminal pH and the ruminal mucosa thickness in bulls fed increasing concentrate levels from 5 to 96%.…”
Section: Ruminal Mucosa Thicknessmentioning
confidence: 99%
“…Although the sample of the animals in the study was considerable, we had investigated just beef cattle of the same sex, breed and stage of breeding, other several variables should be considered seeing if there are differences in RWT and RMST measurements like in dairy cows [21].…”
Section: Discussionmentioning
confidence: 99%
“…Mirmazhari-Anwar et al (2013) [20] reported increasing rumen mucosa thickness when using a transabdominal rumen ultrasound in cannulated bulls fed diets, increasing in concentrate level from 5 to 96% dry matter (DM). Neubauer et al (2018) [21] confirmed the potential of rumen mucosa thickness measurement via ultrasound as a diagnostic tool for subacute rumen acidosis, adjusted for the age or lactation number of the individual dairy cow.…”
Section: Introductionmentioning
confidence: 98%